Skeletal Muscle Metabolism and Performance During Heavy Muscular Contraction in the Isolated Perfused Rat Hindquarter - Spriet, Lawrence L. (My University, 1984)
Direct assessments of the relative contributions of the major energy releasing pathways in human skeletal muscle during heavy exercise are difficult to obtain due to the invasive measurements required. With an isolated muscle preparation the muscles' environment is carefully controlled and all metabolic measurements are directly obtained. For this reason the isolated perfused rat hindquarter model, previously used to study resting muscle metabolism, was developed to examine the metabolism and performance heavily contracting skeletal muscle.
Energy calculations based upon measurements of O₂ uptake (aerobic metabolism), lactate production (anaerobic glycolysis) and CP hydrolysis (alactic anaerobiosis) were made during 20 minutes of repetitive tetanic stimulation. During the initial 5 minutes of stimulation isometric tension production was high but fatigued rapidly and anaerobic involvement in energy production was large (30%), especially in the fast-twitch glycolytic muscle fibers. Muscle glycogenolysis provided the majority of substrate for both anaerobic glycolysis and aerobic metabolism. During the final 15 minutes of stimulation aerobic metabolism dominated (90%) while 60% of peak tension was held, mainly by the fast-twitch oxidative, glycolytic muscle fibers. Glycogen utilization was minimal and intramuscular triacylglycerol became the dominant fuel for oxidative metabolism, contributing 62% of the energy produced.
Perfusions with acidotic mediums (metabolic and respiratory) reduced muscle glycogenolysis and lactate accumulation by 35% during the initial 5 minutes of stimulation. The decreased glycolytic flux reduced the availability of carbohydrate substrate for aerobic metabolism and O₂ uptake decreased. The associated reduction in energy release produced an increased rate of tension decay. Total energy release and tension production were also reduced during acidosis in the final 15 minutes of stimulation. The decreased glycolytic flux appeared to be due to an earlier fall in muscle pH during acidosis and subsequent inhibition of key regulatory enzymes such as phosphorylase and phosphofructokinase. However an alternate hypothesis is that acidosis exerted a direct negative effect on the excitation-contraction coupling mechanism, thereby reducing the need for energy production.
Keywords: Medical Sciences; Medical Sciences